Investigating the effect of the teaching method of peer education in medical students of surgical internship on satisfaction, grade at the end of the section, and implementation ability of education in Kurdistan University of Medical Sciences. - Keivan Sabooni; Madjid Shafiayan; Farzaneh Zarei; Behzad Khalafi (مجله علمی دانشگاه علوم پزشکی کردستان)
Background and Aim: In addition to its challenges, modern methods of education can greatly improve the quality of education by involving students in educational processes. Peer education as one of the new educational methods has shown that it can have an impact on university education and can be more effective compared to the classical teaching method with the lecture method. Therefore, this study was designed and implemented to compare the effectiveness and feasibility of peer education in surgical department discussions. Materials and Methods: In this interventional study, 120 surgical externship students were selected by census method and were evaluated randomly in two groups during two months of training in the surgery department. Both groups received routine training, and in the intervention group, some topics were taught in the form of compiling and presenting class conferences by groups of students. To evaluate the clinical knowledge, the final exam score and the degree of satisfaction, feasibility, and validity of the training were used from a researcher-made questionnaire that was psychometrically evaluated after completing the internship. To validate the tool, the content validation method was used, and reliability according to experts and psychometrics was evaluated by the professors of the group. The data was analyzed using statistical tests by SPSS software version 21. Results: A significant difference was found between the two control and intervention groups in terms of satisfaction, validity, and applicability, and the level of satisfaction, as well as the level of learning, was significantly higher compared to the observation group that was trained by the lecture method(p<0.05); was higher It has also achieved its educational goals, including satisfaction and learning, as well as self-efficacy. Another finding of this study is the difference in the final grade, which was significantly higher in the peer education group than in the classical education group (13.44 vs. 15.21 (p<0.001)). Conclusion: Based on the results obtained in this study, peer-to-peer teaching in the teaching of surgery topics can have a more effective role than classical teaching in terms of gaining satisfaction, ease of implementation, and improving students' grades. However, in this matter, the limitations and special characteristics of learners should be considered.